Epidermal growth factor receptor signaling mediates aldosterone-induced profibrotic responses in kidney - Sheng, Lili; Yang, Min; Ding, Wei; Zhang, Minmin; Niu, Jianying; Qiao, Zhongdong; Gu, Yong (Experimental cell research, 2016)
Aldosterone has been recognized as a risk factor for the development of chronic kidney disease (CKD). Studies have indicated that enhanced activation of epidermal growth factor receptor (EGFR) is associated with the development and progression of renal fibrosis. But if EGFR is involved in aldosterone-induced renal fibrosis is less investigated. In the present study, we examined the effect of erlotinib, an inhibitor of EGFR tyrosine kinase activity, on the progression of aldosterone-induced renal profibrotic responses in a murine model underwent uninephrectomy. Erlotinib-treated rats exhibited relieved structural lesion comparing with rats treated with aldosterone alone, as characterized by glomerular hypertrophy, mesangial cell proliferation and expansion. Also, erlotinib inhibited the expression of TGF-β, α-SMA and mesangial matrix proteins such as collagen Ⅳ and fibronectin. In cultured mesangial cells, inhibition of EGFR also abrogated aldosterone-induced expression of extracellular matrix proteins, cell proliferation and migration. We also demonstrated that aldosterone induced the phosphorylation of EGFR through generation of ROS. And the activation of EGFR resulted in the phosphorylation of ERK1/2, leading to the activation of profibrotic pathways. Taken together, we concluded that aldosterone-mediated tissue fibrosis relies on ROS induced EGFR/ERK activation, highlighting EGFR as a potential therapeutic target for modulating renal fibrosis. •EGFR was involved in aldosterone-induced renal profibrotic responses.•Aldosterone-induced EGFR activation was mediated by MR-dependent ROS generation.•EGFR activated the MAPK/ERK1/2 signaling to promote renal fibrosis.